Kajian Pengaruh Kadar dan Ukuran Kapur dalam Netralisasi Potensi Keasaman Tailing dari Kegiatan Pertambangan Emas - Plucheria Pritta Aquila; Candra Nugraha (Fakultas Teknik, 2023)
AbstractMineral mining activities will leave waste rock known as tailings, which has small particle sizes and can trigger an oxidation reaction of the sulfide minerals contained therein and produce AMD. Laboratory tests have been carried out to determine the effect of the additional lime in terms of rate and particle size to neutralize the acid water formed through qualitative and quantitative mineral testing and static geochemical testing for various combinations of lime rates and sizes. This study used lime with a CaO content of 90.9% and tailings with a sulfur content of 4.88%. Subsequently, the pasta pH-EC, ABA, and NAG tests were conducted on a mixture of lime and tailings with lime sizes ranging from 8-16 to 50-100 mesh and a lime: tailings ratio of 2.5 to 15 kg/ton tailings. The test results show lime with a size of 50–100 mesh with a lime: tailings composition of 15 kg/ton tailings provides the most optimal effect in neutralizing potential acidity from tailings indicated by a pH value of 7.18. This study is expected to provide input in the management of tailings in mining to avoid acidic water which has the potential to dissolve metal content in tailings that have a negative impact.Keywords: AMD, lime content, grain size, Ph, tailing